Degenerative lumbar spinal stenosis treatment with Aperius™ PerCLID™ system and Falena® interspinous spacers: 1-year follow-up of clinical outcome and quality of life. Issue 2 (April 2016) - Masala, Salvatore; Marcia, Stefano; Taglieri, Amedeo; Chiaravalloti, Antonio; Calabria, Eros; Raguso, Mario; Piras, Emanuele; Simonetti, Giovanni
Purpose: Evaluation of the efficacy of the Falena® and Aperius™ PerCLID™ interspinous devices in the treatment of degenerative lumbar spinal stenosis with neurogenic intermittent claudication refractory to conservative treatment. Materials and methods: We retrospectively analyzed data from 24 patients (20 male and 4 female patients; 61 ± 7 years old), treated with an implantation of the AperiusTM PerCLID™ system, and from 35 patients (29 male and 6 female patients; 65 ± 9 years old) treated with the Falena® interspinous device. Patient pain intensity was evaluated by a 10-point visual analog scale (VAS), with a score (ranging from 0 = no pain to 10 = unbearable pain) that was collected before the procedure, at baseline; and at months 1, 6 and 12 after the interventional procedure. The assessment of quality of life (QOL) impairment was evaluated by the Oswestry Disability Index (ODI) questionnaire, which was administered beforehand at baseline; and at months 1, 6 and 12 after the interventional procedure. The vertebral canal area was measured by magnetic resonance imaging (MRI) scans before the treatment and at the one-year follow-up. Results: All patients completed the study with no complications. Both the Falena group and Aperius group of surgery patients showed a statistically significant reduction of their VAS and ODI scores at the 6- and 12-month follow-up ( p < 0.0001). A statistically significant increase in the vertebral canal area was observed both in the group that received Falena ( p < 0.0001) and in the group that received Aperius ( p = 0.0003). At the 1-year follow-up, we observed that there was a higher increase of vertebral canal area in those patients whom were treated with the Falena device ( p < 0.001). Conclusions: The implantation of Falena® and Aperius™ PerCLID™ interspinous devices is an effective and safe procedure, in the medium term.